Conselho Escolar, instrumento de gestão democrática em tempos de políticas neoliberais: experiências em questão no município de Baturité - Assis, Ana Claudia Lima de (2007)
This work aims at investigating the politics of democratic administration found in public schools of the State of Ceara considering the action of School Councils. The research’s investigative goal is fundamentally tied to Brazil’s current social, economic, political and cultural patterns, marked by changes produced by the process of world dominance by capital that requires a redefinition of the State’s role and its relationship with civil society under the aegis of neo-liberal influence. It is shown as a key point to the analysis of the investigative phenomenon the historical context in which neo-liberal political stirrings took place strongly marked by a combination of the democratic/participative process and the structure-adjusting process. In addition, the work aims at sharing with the scientific and academic communities some reflections and conclusions about democratization tools for public schools as produced by the School Councils at a time for adjustments to the neo-liberal power frame as well identifying advancement, limits and possibilities related to this journey that counted on the effective participation of segments involved, such as parents, students, teachers, public servants, administrators and local community which helped promoting the development of a participation-minded pedagogy that produced innovative practices related not only to intra-school relations but also relations between school and community. The methodological procedure included bibliographic survey, documents, as well as qualitative field research in order to detect social knowledge acquired by the several subjects that were involved in the political implementation of democratic administration of public schools through School Councils. The upshot of the empirical investigation as conducted on two bodies of School Councils located in the county of Baturite reveals that democratic administration as offered by the State or as a conquest of civil society is carried out with ambiguities and contradictions, on the one hand questioning governmental policies or legitimating them on the other. In their turn, School Councils are hybrid environments that function spasmodically, but in spite of their small contribution there are real gains seen in a gradual approximation to democratic behavior that signals at amplifying citizenship in school.